Evaluation of Dual Inhibitory Effect of Anagliptin, Ramipril and Lisinopril on Angiotensin-Converting Enzyme and DPP-4 Activities - Abouelkheir, Mohamed (Current Molecular Pharmacology, 2022)
Background: We previously tested two angiotensin-converting enzyme (ACE) inhibitors and two dipeptidyl peptidase-4 (DPP-4) inhibitors for dual enzyme inhibitory effect. Only two DPP-4 inhibitors, linagliptin and sitagliptin, were able to inhibit ACE. Objective: In the present study, we investigated if other inhibitors of ACE or DPP-4 could simultaneously inhibit the activities of both DPP-4 and ACE. Methods: Forty Sprague Dawley rats were used. The control group received only saline. The other three groups were treated with anagliptin, ramipril, or lisinopril. Two different doses were tested separated with a 6-day drug-free interval. Angiotensin II (Ang II) levels and the activities of ACE and DPP-4 were measured from blood samples at baseline and days 1, 10, and 14. After the oral glucose challenge test, levels of the active form of glucagon-like peptide-1 (GLP-1) were measured. Results: Regardless of the dose, anagliptin did not show any inhibitory effect on the activity of ACE or Ang II levels. Concerning ramipril and lisinopril, only a high dose of lisinopril was able to produce a modest reduction of the DPP-4 activity but not enough to inhibit the inactivation of GLP-1. Conclusion: It seems that while most of the ACE inhibitors cannot affect DPP-4 activity, inhibitors of DPP-4 vary in their effects on ACE activity. The selection of DPP-4 inhibitors under different clinical situations should take into account the action of these drugs on ACE.
Keywords: enzyme activity